Atsar al-Qur’an al-Karim fi al-Lughah wa al-Syi’r wa al-Natsr: Dirasah al-Adab al-‘Araby fi ‘Ashr Shadr al-Islam - Aflisia, Noza; Yunus, Badruzzaman M; Musthafa, Izzuddin; Shaleh Atho, Yusuf Ali (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This paper aims to analyze the impact of the Holy Qur'an on the Arabic language, poetry and prose during the early Islam period. The method used in this research is the descriptive analytical method, that is by describing the influence of the Qur'an on the Arabic language, poetry and prose during the period of early Islam. While the approach applied in this research is a historical one in which researchers search for dates related to the influence of the Qur’an on the Arabic language, poetry and prose in the early Islamic period. The results are that the impact of the Qur’an in the Arabic language is to preserve Arabic from loss and to make it a living and immortal language, and to derive many sciences from a gift, such as the science of readings, the science of interpretation, the reasons for revelation, the grammar, the parsing, the sciences of rhetoric, the science of jurisprudence and its origins, and the language has been provided with many vocabulary and meanings such as al-Furqan and polytheism. hypocrisy and so on. The Qur'an was greatly influenced by the language of poets and orators. There are even quotes from the Qur’an such as faith, hypocrisy, blasphemy, prayer, zakat, etc., and also from the contents of the Qur’an such as jihad, advocacy, fighting the opponents of Islam, the Day of Judgment, Heaven, Hell, and so on. The era of early Islam contains the texts of the Qur'an and Hadith. The Qur'an and Hadith in this time have more influence on the book in rhetoric and writing. The Holy Qur'an has had a great impact on the language, styles, and contents of literary production of poets, orators, and the contents of their literary production. Prose is taken from the Qur'an, not poetry.